Estudo bioarqueológico de remanescentes ósseos de um ameríndio da etnia Tupiguarani - Santos, Antônio Sílvio Teixeira dos (2023)
The present research has as its object of study bioarchaeological remnants: bones and artifacts buried with the dead, and dating of an indigenous Tupiguarani ethnicity deposited at the Museum of Natural History of Paraíba. The interdisciplinarity between Medicine and Archeology was used in the study to better understand the way of life of the individual whose population he belonged to no longer exists. Macroscopic observations made it possible to analyze health status, biological profile: age at death and gender. Other data were inferred through anatomical studies of the bones and other artifacts. The funeral trousseau is part of the archaeological and bioarchaeological context, therefore, it is part of the study. Radiocarbon dating revealed that the subject of the study lived in the pre-colonial period, revealing a territorial distribution different from the historical one that limits the Tupiguaranis to the coast of the state of Paraíba, due to the fact that the finding took place in the sertão of Paraíba.